2020
DOI: 10.1177/0192513x20966008
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Combination? The Influence of Work-family Life Courses on Life Satisfaction at Higher Ages among German Women

Abstract: This study analyzed the association between work-family life courses and life satisfaction among 2,542 women aged 60–65 years (born between 1920 and 1957) using German SOEP data and ANOVA models. The results are embedded in a description of the specific role of mothers in Germany (as primary caregivers), different theoretical assumptions (from role theories and theories on cumulative advantages and disadvantages), and prior results (from longitudinal and cross-sectional research). The findings provide strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Employment of aging workforces is consistent with the UN's sustainable development goals. Previous studies have shown that older people who continue to work can improve their life satisfaction [22,25,26] and reemployment after retirement is conducive to improving life satisfaction among older people [27], thus further improving their quality of life. On the other hand, there is a very close relationship between life satisfaction and sustainable employability.…”
Section: Introductionmentioning
confidence: 99%
“…Employment of aging workforces is consistent with the UN's sustainable development goals. Previous studies have shown that older people who continue to work can improve their life satisfaction [22,25,26] and reemployment after retirement is conducive to improving life satisfaction among older people [27], thus further improving their quality of life. On the other hand, there is a very close relationship between life satisfaction and sustainable employability.…”
Section: Introductionmentioning
confidence: 99%